ANALISIS WAKTU TUNGGU PELAYANAN RESEP OBAT RACIKAN DAN NON RACIKAN PADA PASIEN BPJS RAWAT JALAN DI RSUDDr. ACHMAD MOCHTAR BUKITTINGGI - Antin Aulia Lestari; Deswati, M.Farm.,Apt, Khairil Armal,S.Si.,Apt.,SpFRS (Jurnal Kesehatan, 2025)
Waiting time for prescription services is the length of time calculated from the time the patient submits the prescription to the pharmacy staff until the medicine is received by the patient. Based on minimum hospital service standards (SPM RS) Minister of Health Decree No.129/Menkes/SK/II/2008, the waiting time for services for compounded drug prescriptions is ≤ 60 minutes and for non-concocted prescriptions is ≤ 30 minutes. The aim of this research is to analyze the waiting time for prescription services for compounded and non-concocted medicines for BPJS patients at Dr. Achmad Mochtar Bukittinggi Hospital, whether they have met the minimum service standards or not. The method used in data collection is observational, namely directly observing the waiting time for prescription services. Sampling was carried out using a purposive sampling technique. The data obtained by the researchers were 389 recipes consisting of 48 concocted recipes and 341 non-concocted recipes. Based on the results obtained, the waiting time for prescription services at the outpatient pharmacy at RSUD Dr. Achmad Mochtar Bukittinggi has met the minimum service standards (SPM). The average waiting time for service for concocted prescriptions is 53.06 minutes (3,216 seconds) and non-concocted prescriptions is 10.09 minutes (654 seconds). The factors that influence the length of waiting time are the type of prescription, the number of R/, the availability of drugs and facilities that have problems/errors such as prit machines and networks that have experienced problems several times.